Intuitive Strategies Used by Untrained EFL Teachers to Teach Autistic Students (2023)
This project is related to the teaching strategies that teachers intuitively implement in English as a foreign language classes. This, considering the inclusive education guidelines for special needs students in Colombia. The research is focused on different English teachers’ classes and their autistic students in a private inclusive school in Chia - Cundinamarca. Therefore, the objective in this work is to identify the intuitive strategies applied by the teachers without previous knowledge in special needs, in order to deliver their classes into an inclusive environment for the autistic children. That said, it is important to remark that this is a qualitative research, as it is taken into account each experience, opinion and concept in the learning process with autistic children; also, the data collection methods selected were interviews, field notes and observations to obtain more detailed information. In addition, this project include the findings about the strategies that teachers used intuitively, which are divided into different categories such as impact of art as a means of stimulation in the teaching of English, importance of new vocabulary to learn a second language, simplification of explanations, and result of group activities as a means of development in EFL classes. In this way, it is expected this project will be useful in terms of strategies for autistic students, despite the lack of teacher training in this field.